(untitled) (SAARC Journal of Agriculture, 2024)
The tribe Dacini, within the sub-family Dacinae of the Tephritidae family, includes major fruit flies within the genera Zeugodacus, Bactrocera, and Dacus. The Bactrocera spp., which were previously grouped into sub-genera Zeugodacus and Bactrocera, have been treated as separate genera in recent years. These dacine flies are widely spread in fruits and vegetables. The first dacine fruit fly, i.e. D. (Callantra) nepalensis reported in 1964 from Nepal is still a holotype. Altogether, 27 species have been reported in Nepal from three genera–Dacus (6), Zeugodacus (8), and Bactrocera (13), of which 10 species are attracted to cue-lure, 7 species to methyl eugenol, 2 species to zingerone, 1 species to lati-lure and 5 species to more than one lure, while lure for 2 species are unknown. Among them, 7 species are oligophagous pests, 6 species are polyphagous pests, and the pest status of 14 species is unknown. Fruit fly infestation and damage have been recorded in different crops such as; 5 species on cucurbits, 2 species on different fruits, 4 species on different fruits and vegetables, 1 species on citrus fruits, and 1 species on solanaceous vegetables. Three species; Z. cucurbitae, Z. tau, and B. minax, have been recorded from infested fruit cultures of cucurbits and sweet orange too. However, pest status, preferred hosts, and biology of many species remain yet to be explored and reported from Nepal. Further studies are necessary focusing on fruit fly species of economic importance concerning host preference for developing appropriate management strategy. Efforts are needed to identify the fruit fly species that inflict actual damage to the hosts. SAARC J. Agric., 22(1): 1-15 (2024)